Asymptotic Behavior of a Counting Process in the Maximum scheme - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We determine the exact asymptotic behavior of the logarithm of a counting process in the maximum scheme.